Upaya Peningkatan Perilaku Sadar Periodontal Sehat pada Ibu Hamil di Desa Paddinging, Kecamatan Sanrobone, Kabupaten Takalar - Abdi, Muhammad Jayadi; Aldilawati, Sari; Wijaya, Muhammad Fajrin (Idea Pengabdian Masyarakat, 2022)
Oral health of pregnant women affects the condition of the baby they contain. If pregnant women suffer from periodontal infection, they are at risk of giving birth to babies with low birth weight and experiencing premature. We see that the knowledge of pregnant women and those who are currently in the pregnancy program is still very lacking regarding how to maintain and care for dental and oral health. This is a problem in Paddinging Village, so it is important to hold counseling. This service was carried out at the Paddinging Village sub-district office, Takalar sub-district. The method of dedication is by Lectures/counseling, Discussions and questions and answers. As a result of the dedication, we got enthusiastic patients and active respondents in asking questions so that they are committed to always maintaining the cleanliness of their oral cavity, and have routine dental and oral health checks.